The molecular biology of tubulinopathies: Understanding the impact of variants on tubulin structure and microtubule regulation - Hoff, Katelyn J.; Neumann, Andrew J.; Moore, Jeffrey K. (Frontiers in Cellular Neuroscience, 2022)
Heterozygous, missense mutations in both alpha- and beta-tubulin genes have been linked to an array of neurodevelopment disorders, commonly referred to as “tubulinopathies”. To date, tubulinopathy mutations have been identified in three beta-tubulin isotypes and one alpha-tubulin isotype. These mutations occur throughout the different genetic domains and protein structures of these tubulin isotypes, and the field is working to address how this molecular-level diversity results in different cellular and tissue-level pathologies. Studies from many groups have focused on elucidating the consequences of individual mutations; however, the field lacks comprehensive models for the molecular etiology of different types of tubulinopathies, presenting a major gap in diagnosis and treatment. This review highlights recent advances in understanding of tubulin structural dynamics, the roles microtubule-associated proteins (MAPs) play in microtubule regulation, and how these are inextricably linked. We emphasize the value of investigating interactions between tubulin structures, microtubules, and MAPs to understand and predict the impact of tubulinopathy mutations at the cell and tissue levels. Microtubule regulation is multifaceted and provides a complex set of controls for generating functional cytoskeleton at the right place and right time during neurodevelopment. Understanding how tubulinopathy mutations disrupt distinct subsets of those controls, and how that ultimately disrupts neurodevelopment, will be important for establishing mechanistic themes among tubulinopathies that may lead to insights in other neurodevelopment disorders and normal neurodevelopment.